1998
DOI: 10.1002/(sici)1097-0010(199806)77:2<184::aid-jsfa22>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin content in the seeds of several apricot cultivars

Abstract: Eight different cultivars of apricots (Prunus armeniaca L) have been studied regarding the amygdalin content of their seeds to correlate amygdalin content with known phenotypes to determine if the inheritance of this trait is controlled in a discrete or quantitative manner. HPLC determination of amygdalin showed large differences between cultivars with sweet and bitter kernels. Also, some significant differences within groups of bitter and sweet kerneled cultivars were found but they did not correlate with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 5 publications
3
29
0
1
Order By: Relevance
“…Lucas y Sotelo (1984) determinaron el contenido de ácido cianhídrico (obtenido a partir de la hidrólisis de la amigdalina) en semillas de diferentes Prunus, como ciruelo (233 mg/100 g), albaricoquero (136 mg/100 g), cerezo (131 mg/100 g) y manzano (42 mg/100 g). En semillas de albaricoquero, Femenia et al (1995) obtuvieron concentraciones de amigdalina entre 4.400 y 6.500 mg/100 g de muestra seca y Gómez et al (1998) En el caso de la almendra, Corradi y Micheli (1982) determinaron concentraciones de 3.300 mg de ácido cianhídrico/kg de muestra seca. Usai y D'hallewin (1992) determinaron concentraciones de 9.255 mg de amigdalina/kg muestra seca para la variedad amarga Sassari 11 y 1.056 mg/ kg de muestra seca en la variedad dulce Arrubia.…”
Section: Resultados Y Discusiónunclassified
“…Lucas y Sotelo (1984) determinaron el contenido de ácido cianhídrico (obtenido a partir de la hidrólisis de la amigdalina) en semillas de diferentes Prunus, como ciruelo (233 mg/100 g), albaricoquero (136 mg/100 g), cerezo (131 mg/100 g) y manzano (42 mg/100 g). En semillas de albaricoquero, Femenia et al (1995) obtuvieron concentraciones de amigdalina entre 4.400 y 6.500 mg/100 g de muestra seca y Gómez et al (1998) En el caso de la almendra, Corradi y Micheli (1982) determinaron concentraciones de 3.300 mg de ácido cianhídrico/kg de muestra seca. Usai y D'hallewin (1992) determinaron concentraciones de 9.255 mg de amigdalina/kg muestra seca para la variedad amarga Sassari 11 y 1.056 mg/ kg de muestra seca en la variedad dulce Arrubia.…”
Section: Resultados Y Discusiónunclassified
“…1a, 1b). This result was consistent with studies of seeds in several stone trees 18,19 . The amygdalin accumulation in leaves coincided with the growth of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have examined the use of the wild apricot oil in many areas 1,3,4 . Although most of these studies suggest that the wild apricot oil is suitable for human consumption, they have found that wild apricot oil also contains up to 8% amygdalin 5,6 . From our production experience and detection, amygdalin or HCN inevitably enters the apricot oil during the cold pressing process 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Both amygdalin and HCN can cause acute intoxication and chronic syndromes of the human central nervous system. The presence of these toxic substances presents a challenge to the usage of kernel-derived products for human or animal consumption 5 . As few findings reports the toxicological properties of wild apricot oil, we used albino Sprague-Dawley (SD) rats to assess its suitability as edible oil.…”
Section: Introductionmentioning
confidence: 99%